Personal Health Record Software for Neuroendocrine Tumors: Patient-Centered Design Approach - Juan Pablo Hourcade; Michael O'Rorke; Elizabeth Chrischilles; Nicholas J Rudzianski; Brian Gryzlak; Kerry Peterman; Chris Ortman; Sam Wolstencroft; Margaret Bean; Elyse Gellerman; Josh A Mailman; Maryann Wahmann (JMIR Human Factors)
Abstract BackgroundPersonal health record (PHR) software has the potential of aiding with patient engagement and data collection in longitudinal research to better understand the long-term impact of treatments on patients with rare medical conditions. Neuroendocrine tumors (NETs) represent a rare condition with unique challenges related to symptom management, treatment tracking, and patient-provider communication. ObjectiveThis study aimed to design, develop, and evaluate PHR software tailored for patients with NETs as part of a longitudinal research study. Our goal was to create a patient-centered PHR that supports both self-management and research data collection. MethodsThis included activities spanning the entire development lifecycle from identifying user requirements through focus groups and surveys, iterative prototype refinement via cognitive walkthroughs, and usability testing of the functional PHR system. Feedback from patient advocacy organizations and clinical experts further informed PHR development. ResultsThe resulting PHR allows patients with NETs to access condition-specific information, track symptoms, monitor treatment regimens, and share data with health care providers. Patients valued the ability to visualize personal health trends and patterns over time, enhancing both self-management and communication with medical teams. Usability testing indicated high levels of patient satisfaction with the system’s functionality and design. ConclusionsThe development of this PHR demonstrates the value of engaging patients in the design process to ensure that health technologies address real-world needs. Our approach provides a model for designing PHR systems for other rare conditions, highlighting the importance of patient-centered design in supporting both clinical care and longitudinal research.